RISK ASSESSMENT OF BAGGED FERTILIZER UNLOADING ACTIVITY AT TUKS PUSRI BANYUWANGI BRANCH - Purwitasari, Diyah; Sianturi, Intan; Siahaan, Renta Novaliana; Arrofi, Faizal (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
The port is one of the distribution centers for goods in which there are loading and unloading activities. Loading and unloading activities sometimes involve loading and unloading personnel and heavy equipment which raises the potential for hazards that can cause work accidents and damage to goods. The purpose of this research is to conduct a risk assessment using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) method on bagged fertilizer unloading work in the TUKS PUSRI Banyuwangi Branch Port area. The stages of bagged fertilizer unloading work activities include the unloading activity process, which consists of five work stages: opening the ship's hatch, workers (stevedores) entering the hatch, stevedoring, cargodoring, and delivery. The results stated that from a total of 5 work stages, 26 sources of hazards were identified with 6 sources of low risk level hazards at 23%, 7 sources of moderate risk level hazards at 27%, 6 sources of high risk level hazards at 23%, and 7 sources of very high risk level hazards (extreme) at 27%. Control measures that can be implemented are conducting briefings on OHS (Occupational Health and Safety) before starting work activities, supervision of compliance with the use of complete personal protective equipment and also the need for sanctions for workers who do not comply with the rules for using personal protective equipment.